Goodness-of-fit test for discrete and censored data, based on the empirical distribution function - Pettitt, Anthony (1973)
In this thesis two general problems concerning goodness-of- fit statistics based on the empirical distribution are considered. The first concerns the problem of adapting Kolmogorov-Smirnov type statistics to test for discrete populations. The significance points of the statistics are given and various power comparisons made.